2015
DOI: 10.1007/s12640-015-9561-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Uric Acid Levels in Ischemic Stroke Patients

Abstract: The importance and function of serum uric acid (UA) levels in patients with cardiovascular disease or stroke are unclear. We sought to evaluate the appropriate UA levels for stroke patients and the association between endogenous UA levels and clinical outcomes in acute ischemic stroke (AIS) patients, particularly regarding the possible interaction between gender and UA levels with respect to AIS prognosis. We examined 303 patients who had an onset of ischemic stroke within 48 h. Of those, 101 patients received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…However, the results of epidemiological studies investigating the effect of serum UA levels on the prognosis of acute ischemic stroke are conflicting because of previous studies being limited to small single-center series or poor study design. Some studies suggested serum UA was protective for the prognosis of acute ischemic stroke10111213, whereas others indicated that it had no such effect1415 or even increased the risk of poor outcome and future vascular events after acute stroke1617. It is well known that UA levels are higher in men, and a sex-difference in the relationship between serum UA and risk of cardiovascular disease had been reported181920.…”
mentioning
confidence: 99%
“…However, the results of epidemiological studies investigating the effect of serum UA levels on the prognosis of acute ischemic stroke are conflicting because of previous studies being limited to small single-center series or poor study design. Some studies suggested serum UA was protective for the prognosis of acute ischemic stroke10111213, whereas others indicated that it had no such effect1415 or even increased the risk of poor outcome and future vascular events after acute stroke1617. It is well known that UA levels are higher in men, and a sex-difference in the relationship between serum UA and risk of cardiovascular disease had been reported181920.…”
mentioning
confidence: 99%
“…Prolonged aPTT was associated with worse stroke outcome, suggesting it's neuro-protective effect at short time (Kisialioul et al, 2012) [29]. But the INR values in this study were not significantly associated with SSS or MRS, so INR can't be considered in the evaluation of AIS patients of this study, but it is more useful in monitoring thrombolytic therapy to avoid serious cerebral hemorrhage this opinion is in day 90 and smaller infarct volume [18] [36]. In this study we noticed that, the elevated SUA was associated with less severe stroke and better outcome, so high SUA may be an independent predictor of AIS [17] [37].…”
Section: Discussionmentioning
confidence: 67%
“…Another chemical investigation within the predictive panels of AIS is SUA. Its high level is associated with excellent outcomes so it used as adjuvant therapy to thrombolysis [17] [18]. Serum TG is an independent predictor of AIS outcome, but its association with cardio-embolic stroke is not a role [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, higher levels of UA have been associated with gout (24,25), and associations between hyperuricemia and an increased risk of various metabolic disorders have also been described (5,6). In fact, a U-shaped association between extremely low or high UA levels and worse outcome has been described in stroke (10,26). However, it appears that, under conditions of increased oxidative stress, as occurs in acute ischemic stroke, the balance between anti-and pro-oxidant properties shifts to promote neuroprotection (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the serum levels of UA have been observed in several diseases. For example, a low UA level has been detected in stroke (8)(9)(10), multiple sclerosis (MS) (11,12), infections of the central nervous system (CNS) (13,14) and leprosy reaction episodes (15). As regards IM, the number of previous related studies is limited and the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%